Molecular Phylogenetic and Biogeochemical Studies of Sulfate-Reducing Bacteria in the Rhizosphere of Spartina alterniflora - Hines, Mark E. (American Society for Microbiology, 1999)
The population composition and biogeochemistry of sulfate-reducing bacteria (SRB) in the rhizosphere of the marsh grass Spartina alterniflora was investigated over two growing seasons by molecular probing, enumerations of culturable SRB, and measurements of SO(4)(2−) reduction rates and geochemical parameters. SO(4)(2−) reduction was rapid in marsh sediments with rates up to 3.5 μmol ml(−1) day(−1). Rates increased greatly when plant growth began in April and decreased again when plants flowered in late July. Results with nucleic acid probes revealed that SRB rRNA accounted for up to 43% of the rRNA from members of the domain Bacteria in marsh sediments, with the highest percentages occurring in bacteria physically associated with root surfaces. The relative abundance (RA) of SRB rRNA in whole-sediment samples compared to that of Bacteria rRNA did not vary greatly throughout the year, despite large temporal changes in SO(4)(2−) reduction activity. However, the RA of root-associated SRB did increase from <10 to >30% when plants were actively growing. rRNA from members of the family Desulfobacteriaceae comprised the majority of the SRB rRNA at 3 to 34% of Bacteria rRNA, with Desulfobulbus spp. accounting for 1 to 16%. The RA of Desulfovibrio rRNA generally comprised from <1 to 3% of the Bacteria rRNA. The highest Desulfobacteriaceae RA in whole sediments was 26% and was found in the deepest sediment samples (6 to 8 cm). Culturable SRB abundance, determined by most-probable-number analyses, was high at >10(7) ml(−1). Ethanol utilizers were most abundant, followed by acetate utilizers. The high numbers of culturable SRB and the high RA of SRB rRNA compared to that of Bacteria rRNA may be due to the release of SRB substrates in plant root exudates, creating a microbial food web that circumvents fermentation.